Directions to the beach of the dead - Blanco, Richard 1968- (Camino del sol, 2005)
"In his second book of poetry, Richard Blanco explores the universal desire for home through evocative narratives, playful musings, and lyrical power. These poems take us on a relentless journey to Spain, Italy, France, Guatemala, Brazil, Cuba, and New England, as they examine the ideal of home and the connections we seek through place, culture, family, love, and art."--BOOK JACKET.